Editorial Volume 17 Issue 5. Industrial Analysis from Multidimensional Perspectives - Bryna Meivitawanli; Ciorstan Smark (Australasian Accounting, Business and Finance Journal, 2023)
This Special Issue of the Australasian Accounting Business and Finance Journal (AABFJ) comes out of the Industrial Analysis from Multidimensional Perspectives stream of the 3rd International Conference on Organizational Performance Excellence (iCOPE 2023). This conference is held by Binus Business School, Bina Nusantara University. The conference takes on the theme of Ecosystem, Innovation, and Excellence in Enhancing Organizational Resilience and Agility for Sustainability and welcomes the submission of research papers focused on any industry. Therefore, this special issue provides industrial analyses from multidimensional perspectives. Each industry has its own unique identity. Therefore, it is important to conduct industry-level analysis to develop better and more effective business strategies.
Keywords: Multidimensional Perspectives; SDGs Publishers Compact; SDGs; Special Issue 3rd International Conference on Organizational Performance Excellence (iCOPE 2023); Editorial Volume 17 Issue 5 -